Mobility, multiculturalism and social inclusion of migrants in South African communities - Thabiso Lucky Malatji (Insights into Regional Development, 2024)
This empirical study examines integration and international human mobility in South African communities. Like any other international actor, South Africa draws many people from around the globe. The study's two main goals are to ascertain how migration affects integration in the host communities and the essential role that multiculturalism plays in these communities. The culture and languages of the migrants are brought with them when they relocate to South Africa. South Africa welcomes its diversity and is a multicultural nation by nature. Additionally, migrants that relocate to South Africa integrate with the host communities, upholding their cultural traditions and proudly speaking their native tongues. The bulk of the immigrants in South Africa, numbering in the hundreds or even millions, are from the Southern African Development Communities (SADC). This qualitative investigation was carried out immediately in the provinces of Mpumalanga and Limpopo. The researcher held Focus group talks in this study with immigrants from various African nations. Additionally, a blindfolded focus group discussion was led by local community members. The study's conclusions showed that immigrants easily integrate into host communities with a common language and culture with South Africans. The study concludes that migration is a worldwide phenomenon and that there will always be transnational human mobility among nations due to globalisation. According to the report, host communities should keep welcoming immigrants and giving them the freedom to live according to their traditions and speak their tongue.